ANALISIS DAYA DUKUNG TIANG BOR (BORED PILE) PADA STRUKTUR PYLON JEMBATAN SOEKARNO DENGAN PLAXIS 3D - Harsanto, Christian; Manoppo, Fabian J.; Sumampouw, J. E. R. (Sam Ratulangi University, 2015)
All construction is engineered for resting on the ground should be supported by a foundation. Foundation serves as the support of the building and continue building loads on it to ground layer sufficient carrying capacity. In planning the foundation on the bridge pylon Dr. Ir. Soekarno used types of foundation pile (bored pile) because the structure of the soil at the location of the pylon is generally composed of loose sand soil or soft clay. In analyzing the bearing capacity of the foundation pile (bored pile) used two ways namely static and PLAXIS 3D. Static way a correlation analysis calculations using formulas that already exist or that are generally often used. While PLAXIS 3D is a finite element program for geotechnical applications where land use models to simulate the behavior of soil. Results of capacity analysis by means of static and Plaxis 3D produces the best configuration is setup in a way satis I. Analysis: N = 17.563 tonnes, Q = 4.329 tons, M = 6.615 ton-m, S = 0.087 m, Yo = 0.044 m. While the analysis with Plaxis 3D: N = 14.320 tonnes, Q = 25.800 tons, M = 5.340 ton-m, S = 0.025 m, Yo = 0.023 m. Keywords : Bored Pile, Bearing Capacity, Static, Plaxis 3D.